Microparticles-Mediated Vascular Inflammation and its Amelioration by Antioxidant Activity of Baicalin - Keshav Raj Paudel; Dong-Wook Kim (Antioxidants, 2020)
Microparticles (MPs) are extracellular vesicles (0.1–1.0 μm in size), released in response to cell activation or apoptosis. Endothelial microparticles (EC-MP), vascular smooth muscle cell microparticles (VSMC-MP), and macrophage microparticles (MØ-MP) are key hallmarks of atherosclerosis progression. In our current study, we investigated the potent antioxidant activity of baicalin to ameliorate MP-induced vascular smooth muscle cell (VSMC) dysfunction and endothelial cell (EC) dysfunction, as well as the production of inflammatory mediators in macrophage (RAW264.7). In our study, baicalin suppressed the apoptosis, reactive oxygen species (ROS) generation, NO production, foam cell formation, protein expression of inducible nitric oxide synthase and cyclooxygenase-2 in MØ-MP-induced RAW264.7. In addition, VSMC migration induced by VSMC-MP was dose-dependently inhibited by baicalin. Likewise, baicalin inhibits metalloproteinase-9 expression and suppresses VSMC-MP-induced VSMC proliferation by down-regulation of mitogen-activated protein kinase and proliferating cell nuclear antigen protein expressions. Baicalin also inhibited ROS production and apoptosis in VSMC. In EC, the marker of endothelial dysfunction (endothelial senescence, upregulation of ICAM, and ROS production) induced by EC-MP was halted by baicalin. Our results suggested that baicalin exerts potent biological activity to restore the function of EC and VSMC altered by their corresponding microparticles and inhibits the release of inflammation markers from activated macrophages.